BIODIVERSITYAND DYNAMICS OF MACRO-INVERTBRATE POPULATIONS IN WHEAT-WEEDS AGRO-ECOSYSTEM OF PUNJAB (PAKISTAN) - M. N. Abbas; S. A. Rana; M. Mahmood-ul-Hassan; N. Rana; S. Kausar; M. Iqbal (Journal of Animal and Plant Sciences, 2014)
This study documented diversity and dynamics of foliage macro-invertebrates sampled from edges and centers of wheat- weeds agro-ecosystem of district Faisalabad (30° 31.5 N and 73° 74 E; 184.41 m l). A total of 4,228 foliage of macro-invertebrates belonging to phylum Arthropoda (92.41%) and Mollusca (7.59%) were recorded. Diptera (27.65%), Hemiptera (27.58%), Coleoptera (18.21%) and Hymenoptera (7.36%) were dominant while Orthoptera, Neuroptera, Lepidoptera and Araneae collectively formed (11.62%) arthropods. Mollusca constituted only of pulmonate gastropods (7.59%). The overall diversity was (H′ = 3.36), that varied seasonally at statistically significantly level. Maximum diversity was recorded in autumn (H′ = 3.57), that was followed by spring (H′ = 3.23) and winter (H′ = 3.09). In contrary to the general findings, Diversity of macro-invertebrate populations in the center (Hˈ= 3.363) was significantly higher than the edges (Hˈ= 3.299) of the fields (p = <0.001).Moreover the richness (S= 58), diversity (H´= 3.23) and evenness (E= 0.79) was recorded higher on wheatcompared to the richness (S= 61), diversity (H´= 3.16) and evenness (E = 0.77) on weeds in wheat-weeds agro-ecosystem.
Keywords: Arthropods; Flora; faunal population; Mixed crop zone; Ecology; population interaction